Rekonstruksi Nilai Kearifan Lokal dalam Sistem Kewarisan Adat Perspektif Hukum Islam pada Masyarakat Sumenep Madura - Busairi; Khalilullah (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2024)
This study examines the system of distribution of inheritance property in the Sumenep-Madura community through two focus research problems: first, how the system of distribution of inheritance property in the Sumenep Madura community? Second, how does Islamic law view the division of inheritance property in the Sumenep-Madura community? As an analytical material, this research uses the theory of Hazairin's concept of inheritance. There are two findings in this study: first, the division of inheritance in Madura through individual inheritance system and the division of inheritance through majorate inheritance system; second, in Hazairin's view, the inheritance system applied to the Sumenep community is in accordance with the spirit of Islamic law, namely the Quran. The division of inheritance property in the community in Madura, distributed in various systems of inheritance, not only with the system of Islamic law (fiqh) but also based on the system of customary inheritance law or custom. This customary inheritance law system is the most widely applied because it is considered more in accordance with the values of custom and tradition of the community.